2016
DOI: 10.1063/1.4959031
|View full text |Cite
|
Sign up to set email alerts
|

On-chip clearing of arrays of 3-D cell cultures and micro-tissues

Abstract: Three-dimensional (3-D) cell cultures are beneficial models for mimicking the complexities of in vivo tissues, especially in tumour studies where transport limitations can complicate response to cancer drugs. 3-D optical microscopy techniques are less involved than traditional embedding and sectioning, but are impeded by optical scattering properties of the tissues. Confocal and even two-photon microscopy limit sample imaging to approximately 100-200 lm depth, which is insufficient to image hypoxic spheroid co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 49 publications
0
36
0
Order By: Relevance
“…The results demonstrated that the method induces a minimal reduction of the size of the spheroids, that is, the ratio of spheroids area before and after the clearing was 1.02 (Grist et al, 2016). The results demonstrated that the method induces a minimal reduction of the size of the spheroids, that is, the ratio of spheroids area before and after the clearing was 1.02 (Grist et al, 2016).…”
Section: See Deep Brainmentioning
confidence: 90%
See 3 more Smart Citations
“…The results demonstrated that the method induces a minimal reduction of the size of the spheroids, that is, the ratio of spheroids area before and after the clearing was 1.02 (Grist et al, 2016). The results demonstrated that the method induces a minimal reduction of the size of the spheroids, that is, the ratio of spheroids area before and after the clearing was 1.02 (Grist et al, 2016).…”
Section: See Deep Brainmentioning
confidence: 90%
“…The results demonstrated that the method induces a minimal reduction of the size of the spheroids, that is, the ratio of spheroids area before and after the clearing was 1.02 (Grist et al, 2016). An analysis of the average FUCCI fluorescence intensity as a function of penetration depth into the sample demonstrated that the SeeDB method allowed to image the spheroids at depths greater than 250 μm, while the imaging of noncleared spheroid was limited to about 150 μm (Grist et al, 2016). The transparency was slightly improved since the light transmittance increased to about 5.5% in the cleared spheroids (Grist et al, 2016).…”
Section: See Deep Brainmentioning
confidence: 96%
See 2 more Smart Citations
“…The trapping mechanisms to load samples within the device vary depending on the design (Fig. 1A) and can combine many mechanisms studied by different authors, such as i) sedimentation trapping, where waiting for the tissue to settle into an extrusion from a channel traps it 710 ; ii) resistive trapping, which exploits preferential flow to guide samples into traps 1116 ; iii) inertial trapping, which uses focusing flows or sharp turns to trap samples in channel recesses 17–19 ; iv) dielectrophoretic trapping, where the difference in permittivity between the fluid and tissue is exploited to trap it in an electric field 20, 21 ; v) and open-microfluidic channel networks, which create hanging droplets in which samples are trapped or synthesized 22, 23 .
Figure 1Basic MST designs: ( A ) MST operation with schematics of different trapping mechanisms: resistive, dielectrophoretic, inertial and sedimentation trapping; blue axis is parallel to gravity. The picture of the western hemisphere of earth on a transparent background was solely created by NASA and is in the public domain in the United States.
…”
Section: Introductionmentioning
confidence: 99%